Practice to resolve in social issues the process of going to socialism in Vietnam today - Nguyễn Công Đức (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
In the process of world history development, any social regime pays special attention to the sustainable development of the nation and its people. Historical reality shows that in order to build a sustainable economic development, one of the top issues of concern must be associated with solving social issues. Good resolution of social issues is one of the major undertakings and solutions to the socio-economic development of our Party and State. Within the scope of this article, the author investigates the inevitability, importance, practice and direction of solving social problems in Vietnam today.